Penggunaan Media Pembelajaran Muthala’ah Berilustrasi dengan Aplikasi Dreamina untuk Meningkatkan Nilai Muthala’ah Santriwati Kelas 4 Kulliyatul Mu’allimin Al-Islamiyah di Pondok Pesantren Muhammadiyah Darul Arqam Patean, Kendal (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
Muṭāla'ah is one of the basic materials in learning Arabic that aims to improve reading and comprehension of texts. However, in practice, it is still found that students have difficulties in understanding reading texts so that learning tends to be less interesting and less optimal. This study aims to determine the effectiveness of the use of illustrated Muṭāla'ah media based on the Dreamina application in improving the Maharah Qira'ah of 4th grade students of KMI Pondok Pesantren Muhammadiyah Darul Arqam Patean Kendal. The research method used is quantitative with an experimental approach using a Quasi Experiment design in the form of Non Equivalent Control Group Design. The research population is all students of class 4 KMI totaling 122 people with saturated sample techniques, namely class 4C as an experimental class of 25 students and class 4D as a control class of 24 students. Data collection techniques include tests, observations, and documentation, while data analysis uses normality tests, homogeneity tests, and Independent Samples T-Test hypothesis tests with the help of SPSS. The results showed that the t-test value was -2.718 with a significance of 0.009 < 0.05 so that there was a significant difference between the experimental and control classes. Thus, the use of illustrated Muṭāla'ah media based on the Dreamina application is effective in improving Muṭāla'ah learning outcomes, as well as providing implications that the development of illustrated technology-based media can increase the effectiveness of Arabic language learning and optimize the learning outcomes of students.